The association between ST8SIA2 gene and behavioral phenotypes in children with autism spectrum disorder - Yang, Xiaolei; Li, Lin; Chai, Xuejiao; Liu, Jicheng (Frontiers in Behavioral Neuroscience, 2022)
Objective: Some population and animal studies have indicated an association between the ST8SIA2 gene and autism spectrum disorder (ASD). However, there is limited information on the correlation between ST8SIA2 and autistic behavioral symptoms. Method: In this study, 69 ASD and 76 normal control children who were age- and sex-matched were recruited. ST8SIA2 expression and methylation levels were measured by qRT–PCR and pyrosequencing, respectively, and the behavioral phenotypes of ASD children were assessed. Result: The ASD group had lower ST8SIA2 gene expression levels than the control group (p=0.006). Moreover, ST8SIA2 expression levels were positively correlated with daily life skills (rs=0.381, p=0.008) and negatively associated with stereotyped behaviors in the ASD group (rs=-0.510, p=0.004). The methylation levels of the Chr. 15: 92984625 and Chr. 15: 92998561 sites of the ST8SIA2 gene in ASD children were higher than those of the controls. The Chr. 15: 92984625 site was positively correlated with the stereotyped behaviors of ASD children (r=0.41, p=0.039). Conclusion: This study provide a scientific basis to elucidate the relationship between the ST8SIA2 gene and behavioral phenotypes of ASD.